Effect of fluoxetine on the inhibition of adenylate cyclase activity in foskolin-stimulated MLTC-1 leydig cells - Mong Diep, Nguyen Thi; Bich Hang, Nguyen Thi; Cong Minh, Nguyen Le; Thanh Son, Tran; Thuy Duong, Nguyen (Vietnam Journal of Biotechnology, 2020)
Fluoxetine (FLX), a widely used antidepressant primarily acting as a selective serotonin reuptake inhibitor, has been shown to exhibit other mechanisms of action in various cell types. Cyclic adenosine monophosphate (cAMP) is a second messenger used for intracellular signal induction. Cyclic AMP is a nucleotide synthesized within the cell from adenosine triphosphate by the adenylyl cyclase enzyme, and is inactivated enzymatically to 5′AMP by hydroxylation with a group of enzymes called phosphodiesterase. The aim of this study was to determine the effects of FLX on MLTC-1 Leydig cells on intracellular cyclic AMP response to forskolin (FSK). MLTC-1 cells were incubated at 37°C in media supplemented with or without different doses of FLX (0, 0.156, 0.3125, 0.625, 1.25, 2.5, 5 and 10 µM). We then looked for how the concentration of FLX for a short-time (2 hours) and a long-time (24 hours) affects the concentration of intracellular cyclic AMP response to FSK and ATP levels on MLTC-1 cells. Our results show that FLX decreased the intracellular cAMP response to FSK depending on FLX concentration. FLX decreased significantly cAMP levels only at 10 µM after 2 hours of incubation but after 24 hours of incubation FLX caused an effect on cAMP levels at 5 µM and at 10 µM. Moreover, as expected, FLX also caused a decline of steroidogenesis, which is under the control of cAMP and ATP levels in the cells. Taken together, these findings demonstrate that the inhibition of cAMP synthesis by FLX is dose-dependent, and that FLX also inhibited hormone-induced steroidogenesis in MLTC-1 cells.